2009
DOI: 10.2190/pm.39.4.e
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of Decisional Capacity Determinations in an Academic Medical Center

Abstract: The MMSE was a useful predictor of capacity determination by PSM personnel, but using MMSE alone results in a number of erroneous determinations. Cognitive disorders were the most common primary psychiatric diagnoses in decisional capacity cases. Primary teams tended to be more accurate when they found patients to lack capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…However, the findings of CIPOLD have contributed to the accumulating body of evidence about the importance of the MCA for patients. Studies have reported that 40-70 per cent of medical in-patients (Raymont et al, 2004;Kahn et al, 2009), and 60 per cent of psychiatric inpatients (Owen et al, 2008) do not have capacity to make decisions about their treatment, suggesting that the link identified by CIPOLD between poor understanding of, and adherence to the MCA by health and social care professionals, and premature deaths of people with ID is likely to have wider relevance beyond people with ID. The MCA has been law since 2007 and, despite advice and toolkits for health and social care professionals, there is an apparent widespread practice gap in understanding and using the MCA for people with ID.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of CIPOLD have contributed to the accumulating body of evidence about the importance of the MCA for patients. Studies have reported that 40-70 per cent of medical in-patients (Raymont et al, 2004;Kahn et al, 2009), and 60 per cent of psychiatric inpatients (Owen et al, 2008) do not have capacity to make decisions about their treatment, suggesting that the link identified by CIPOLD between poor understanding of, and adherence to the MCA by health and social care professionals, and premature deaths of people with ID is likely to have wider relevance beyond people with ID. The MCA has been law since 2007 and, despite advice and toolkits for health and social care professionals, there is an apparent widespread practice gap in understanding and using the MCA for people with ID.…”
Section: Discussionmentioning
confidence: 99%
“…There was no family present at bedside, and he would not provide information to contact them because he "did not want to worry them." The patient's score on the MMSE was 25, which was above the cut-offs of both 21 and 24 described by Kahn et al 4 During his initial evaluation, it was determined that the patient was able to understand his medical situation, manipulate the information, evidence a choice about his treatment plan, and appreciate the situation and its consequences. Given that he was able to meet these standards of capacity, he was found to have the capacity to refuse surgery at that time and to accept intravenous antibiotic treatment to prevent infection (ie, meningitis).…”
Section: Case Descriptionmentioning
confidence: 81%
“…The MMSE is useful in predicting medical decision-making capacity when used in conjunction with other evaluation methods, but it can be misleading when used alone. 4 Kahn et al demonstrated that using an MMSE cut-off score of < 21 is 100% specific and 69% sensitive for identifying patients without capacity, whereas a score of < 24 is only 90% specific and 83% sensitive for identifying patients without capacity. 4 Similar results have been reported elsewhere, 5,6 suggesting that there seems to Illogical thought processes Denial as a defense mechanism Delusions Psychosis Impaired communication skills be a "gray zone" for scores in the middle range of the MMSE that are not predictive of a patient's medical decision-making capacity.…”
Section: The Four Standards Of Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus an assessment of subjects’ decisional capacity may be required prior to completing the informed consent process. A review of the literature surrounding consent of older adults with cognitive limitations suggests using instruments such as, the Mini-Mental Status Exam (MMSE) or the MacArthur Competence Assessment tool for Clinical Research to determine the decisional capacity of an older adult with mild to moderate cognitive impairment (Black et al, 2008; Jefferson et al, 2008; Kahn, Bourgeois, Klein, & Iosif, 2009; Rubright et al, 2010). Furthermore, adding a clinical assessment component can improve prediction of decisional capacity among adults with cognitive disorders (Kahn et al, 2009).…”
Section: Methodological Issuesmentioning
confidence: 99%